(untitled) (Linguostylistic Studies, 2015)
The article is devoted to the detailed description of the Ukrainian components of translation which have no equivalents and present close connection with the original. The material for the analysis was Mykhailo Stelmakh’s stories “The geese are flying” and “The holy supper” and its translation into Russian. The overcoming of language barrier in the translation mainly lies in the creative encoding of the words with expressive ethnocultural colouring. Therefore, the original components, that have no equivalents in any translation, are a justifiable and natural phenomenon. In the translations of close related Slavic languages the possibilities of encoding such units are much bigger than in case with unrelated languages. The following formations, which cannot be translated, have been researched: anthroponyms, words-realities (historical, everyday), pseudorealities, idioms, proverbs, definite word forms and grammatical units. It is shown, that the major ways of reproduction of specific Ukrainian components in this Russian translation are transcription and transliteration, modelling words and constructions after foreign patterns, and also using the quotations from the original language. Key words: theory of translation, artistic translation, a component without an equivalent, encoding, modelling words and constructions after foreign patterns. References